Health Information Systems New Shifts and Emerging Trends in Health IT Infrastructures - Bréant, C.; Section Editor for the IMIA Yearbook Section on Health Information Systems (Yearbook of Medical Informatics, 2009)
Objectives Summarize excellent current research in the field of Health Information Systems.Method Synopsis of the articles selected for the IMIA Yearbook 2009.ResultsFive papers from international peer reviewed journals have been selected for the section on health information systems. They concentrate on topics such as personal health records, the comparison of IT infrastructures in hospitals from different countries, hospital to hospital IT outsourcing partnership, and the wireless monitoring of patients.Conclusions The elected articles highlight the new shifts in health information management and challenges faced by hospitals regarding IT infrastructures.
Keywords: Medical informatics; International Medical Informatics Association; health information systems